2020
DOI: 10.1080/00140139.2020.1807615
|View full text |Cite
|
Sign up to set email alerts
|

A framework for studying risk factors for lower extremity musculoskeletal discomfort in nurses

Abstract: Lower extremity musculoskeletal discomfort (MSD) is prevalent, but understudied, in nurses. A comprehensive, theoretical, aetiological model of lower extremity work-related MSD in hospital in-patient staff nurses was developed through a review of the literature to provide a framework for aetiological and intervention research. The framework informed the design of a survey of 502 hospital staff nurses. Symptom prevalence ranged from 32% in hip/thigh to 59% in ankle/ foot regions. Logistic regression modelling u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…The most common study designs were cross-sectional ( n = 22; 57.89%). As for gray literature, two doctoral theses were retrieved (Li, 2017; Reed, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common study designs were cross-sectional ( n = 22; 57.89%). As for gray literature, two doctoral theses were retrieved (Li, 2017; Reed, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In a mixed-methods study with 20 nurses from medical/surgical and intensive care unit (ICU) wards, Li, Sommerich, and Chipps (2020) reported 53.7% of shift time was spent standing, 14.7% of shift time walking in ICU wards, and 56.3% of time spent standing and 14.03% of time walking for the latter. For ICU wards, the average time on foot, including time standing and walking, is 68.3%, whereas for medical/surgical wards, the value is slightly higher (70.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Nearly two-thirds of nurses working in hospitals in the United States had ankle-foot pain, with 24.8% of them reporting that it interferes with their daily activities. 15 A cross-sectional study conducted in south Brazil among nurses working in the orthopedic setting showed that the prevalence of ankle-foot pain was 55.2%. 16 Ankle-foot pain was the most common work-related musculoskeletal disorder for surgical workers in Europe, causing 2.4% of nurses to miss work, 1.4% to require hospitalization, 52.9% to have their daily work life negatively impacted, 2.9% to change the workplace, and more than half of nurses to use medication as a result of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies done globally, age, body mass index, gender, having multiple underlying foot conditions, working area, working hours per week, prolonged standing, working in night shift, lifting and lowering heavy loads, physical and psychological work demand, job control, job stress, and social support were major factors for nurse’s ankle-foot pain. 14 , 15 , 23 , 25 , 27 , 32–34 So, increasing the number of staff, minimizing working hours, using safety devices to lift and lower objects, and applying ergonomic principles might be the potential interventions to alleviate ankle-foot pain.…”
Section: Introductionmentioning
confidence: 99%
“…6 Burnout has also been shown to be associated with musculoskeletal symptoms in health care workers, as has low job satisfaction, low job control, and low support from supervisors. 7,8 Moral injury is a relatively new outcome of concern in health care workers. In many ways, the experience of an individual suffering from moral injury differs from that of an individual suffering from PTSD, and therefore, a different clinical and therapeutic approach should be taken in their treatment.…”
mentioning
confidence: 99%